Budaya Fanbase Dan Hiperrealitas Komunikasi Politik Di Tiktok Telaah Figur Bahlil Lahadalia - Mira Natalia Pellu (Communicology: Jurnal Ilmu Komunikasi, 2026)
Introduction: The rapid development of TikTok as a visual- and algorithm-driven platform has transformed patterns of political communication on social media. Political figures are no longer primarily presented through policy or formal argumentation but through visual representations that build emotional proximity with digital audiences. Previous studies have focused more on political personal branding and popular fanbase culture, while research on political fanbases as producers of hyperreality on TikTok remains limited. Objective: This study aims to analyze the production of political hyperreality regarding Bahlil Lahadalia through TikTok fanbase culture. Method: This research employs a qualitative approach with a digital netnography design on two TikTok accounts, @Kingbahlillahadalia and @kandabahlil.update. Data were collected through digital observation of videos, captions, music, hashtags, visual edits, and audience interactions from January to April 2026. Results: The findings show that Bahlil is represented as a digital persona that is humorous, inspirational, youth-oriented, and authoritative rather than a formal policy actor. Fanbase culture and TikTok algorithms intensify emotional engagement, turning political communication into a visual-affective experience. Conclusion: TikTok fanbases construct political hyperreality through visual production mediated by algorithms and participatory digital culture.   ABSTRAK Pendahuluan: Perkembangan TikTok sebagai platform berbasis visual dan algoritma telah mengubah pola komunikasi politik di media sosial. Figur politik tidak lagi hadir terutama melalui kebijakan atau argumentasi formal, tetapi melalui representasi visual yang membangun kedekatan emosional dengan audiens digital. Penelitian sebelumnya lebih banyak membahas personal branding politik dan budaya fanbase populer, sementara kajian mengenai fanbase politik sebagai produsen hiperrealitas di TikTok masih terbatas. Tujuan: Penelitian ini bertujuan menganalisis produksi hiperrealitas politik terhadap figur Bahlil Lahadalia melalui budaya fanbase di TikTok. Metode: Penelitian ini menggunakan pendekatan kualitatif dengan desain netnografi digital pada dua akun TikTok, yaitu @Kingbahlillahadalia dan @kandabahlil.update. Data diperoleh melalui observasi video, caption, musik, hashtag, visual, dan interaksi audiens selama Januari–April 2026. Hasil: Temuan menunjukkan bahwa figur Bahlil direpresentasikan sebagai persona digital yang humoris, inspiratif, dekat dengan generasi muda, dan berwibawa dibanding aktor kebijakan formal. Budaya fanbase dan algoritma TikTok memperkuat keterlibatan emosional sehingga komunikasi politik menjadi pengalaman visual-afektif. Kesimpulan: Fanbase TikTok membentuk hiperrealitas politik melalui produksi visual yang dimediasi algoritma dan budaya partisipatif.